The use of augmented reality to improve students' geometry concept problem-solving skills through the STEAM approach - Nindiasari, Hepsi; Pranata, Muhammad Farhan; Sukirwan, Sukirwan; Sugiman, Sugiman; Fathurrohman, Maman; Ruhimat, Agus; Yuhana, Yuyu (Jurnal Infinity, 2024)
This research develops learning media with a Science, Technology, Engineering, Art, Mathematics (STEAM) approach based on Augmented Reality (AR) to improve students' mathematical problem-solving abilities on geometric concepts. This method uses design-based research (DBR). The development stages consist of needs assessment and literature review, design and development, user testing to analyze user responses and evaluation and examination of the media devices being developed. The research subjects for expert tests included media experts and education experts, practicality tests for teachers, response tests for ten high school students, and examination stage tests for 30 high schools in Indonesia. The instruments used were media expert questionnaires, education expert questionnaires, practicality questionnaires, and tests. The media developed is called Augmented Reality Mathematics (ARM). The results of this research are 1) ARM media expert test in the very good category, 2) ARM educational media expert test in the very good category, 3) ARM media practicality test in the good category, 4) responses from students who use ARM media in the very good category, and 5) ARM media can improve mathematical problem-solving abilities in the moderate category. The findings of this research are that AR media is effectively used to improve students' problem-solving abilities in medium-category geometry concepts using the STEAM approach. This research concludes that using ARM media with STEAM learning can improve problem-solving abilities in geometric concepts.